2017
DOI: 10.1002/nme.5549
|View full text |Cite
|
Sign up to set email alerts
|

Topology optimization with additive manufacturing consideration for vehicle load path development

Abstract: Topology optimization has been widely studied and implemented as a powerful conceptual design tool in various engineering applications. However, the result from topology optimization has posed an implementation challenge to engineers because of the complexity of converting obtained solution into computer-aided design data and then fabricating it into real parts. Over the past few years, the advanced additive manufacturing technology with new materials and higher resolution output capabilities has opened numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…The results also showed that the part with comprehensive structures and architectures could be fabricated by additive manufacturing (Tao and Ming, 2016;Langelaar, 2016;Wu et al, 2017;Chuang et al, 2017). And, the SLM process is suitable for fabricating the personalized implant with customized external shape and complicated internal structures.…”
Section: Discussionmentioning
confidence: 89%
“…The results also showed that the part with comprehensive structures and architectures could be fabricated by additive manufacturing (Tao and Ming, 2016;Langelaar, 2016;Wu et al, 2017;Chuang et al, 2017). And, the SLM process is suitable for fabricating the personalized implant with customized external shape and complicated internal structures.…”
Section: Discussionmentioning
confidence: 89%
“…Currently, three-dimensional (3D)-printing technologies are revolutionizing the design and manufacturing of products in many engineering fields, including aerospace [1,2], biotechnology [3], civil engineering [4,5], and automotive engineering [6,7]. The advantages of these techniques include the possibility of considering new shapes that cannot be obtained directly with classical manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing also known as 3D printing has established itself as a form of potentially disruptive manufacturing technique over the recent years. This technique has shown its potential in a variety of industrial domains such as automotive [4,12], medical engineering [5,15], aerospace [3,13] etc. Additive manufacturing process follows a layer by layer build up process which gives an entirely different nature to this technique in comparison to classical methods of fabrication.…”
Section: Introductionmentioning
confidence: 99%